1999
DOI: 10.1088/0953-4075/32/24/317
|View full text |Cite
|
Sign up to set email alerts
|

Ionization of argon and krypton by positron impact

Abstract: Total single and double ionization cross sections for argon and krypton by positron impact have been measured for projectile energies ranging from threshold to ∼1 keV. The single ionization cross sections are seen to behave as expected, showing large contributions from positronium formation at low energies. In the double ionization cross sections there seems to be a lack of positronium formation at threshold, while a clear contribution from the process is seen at intermediate energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…This stems from the differences in electron-atom and positron-atom interacting potentials. In figure 2(f), we compare our σ ion results with the experimental data [76,77] and other theoretical results [78,79]. Our results produce a good [86]; broken line (olive), [87]; dasdot-dashed (blue), [88].…”
Section: Results and Analysismentioning
confidence: 52%
See 1 more Smart Citation
“…This stems from the differences in electron-atom and positron-atom interacting potentials. In figure 2(f), we compare our σ ion results with the experimental data [76,77] and other theoretical results [78,79]. Our results produce a good [86]; broken line (olive), [87]; dasdot-dashed (blue), [88].…”
Section: Results and Analysismentioning
confidence: 52%
“…The thick-solid lines (red) are the present results. The experimental data are from[10,11,[72][73][74][75][76][77] and other theoretical calculations are due to Green et al[19], Campeanu et al[78] and Laricchia[79].…”
mentioning
confidence: 99%
“…For many decades experimental data for positron, electron, and proton impact have been compared in order to provide insight into these effects and to test theoretical models and provide a deeper understanding of the interactions and dynamics. For example, comparing positron and electron impact has shown that at high velocities the total cross sections for single target ionization are nearly identical, whereas the double ionization cross sections for electron impact are roughly a factor of 2 larger [1]. Recent studies [2] also imply that for single ionization of heavier atoms there may be differences between electron and proton impact.…”
mentioning
confidence: 99%
“…(We should point out, however, that a recent study performed by Cavalcanti et al [3] imply that differences due to projectile mass or charge occur in single ionization of heavy atoms.) In contrast, a comparison between positron and electron impact show that double ionization cross sections for electron impact are about 2 times larger [4]. Thus, positron impact studies combined with electron impact information provide additional insight into the kinematics and mechanisms associated with inelastic atomic interactions.…”
Section: Introductionmentioning
confidence: 99%